O Brasil e o Acordo UE-Mercosul: políticas de conteúdo regional e cadeias produtivas regionais e globais - Bertoloni, Michele Cristina Vasques Bertoloni (2023)
The text analyzes the agreement signed between MERCOSUR and the European Union, focusing on the possible effects of the agreement on the Brazilian economy resulting in the integration of Brazil in value chains. The analysis takes as its starting point the history of integration of MERCOSUR and the European Union, addressing the concept of value chains and their relationship with the regional content policies negotiated in the trade agreements that Brazil is a party to. The objective is to assess how the rules of origin negotiated in trade agreements can encourage preferential access to markets and, consequently, leverage Brazil's international insertion in value chains. The exploratory methodology was developed with the analysis of documents and review of the bibliography on the subject. In this sense, the validation of the arguments will consist of the analysis of the text negotiated between MERCOSUR and the European Union